2009
DOI: 10.1002/anie.200805257
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Photon Absorption and the Design of Two‐Photon Dyes

Abstract: Two-photon absorption has important advantages over conventional one-photon absorption, which has led to applications in microscopy, microfabrication, three-dimensional data storage, optical power limiting, up-converted lasing, photodynamic therapy, and for the localized release of bio-active species. These applications have generated a demand for new dyes with high two-photon absorption cross-sections. This Review introduces the theory of two-photon absorption, surveys the wide range of potential applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
1,504
1
19

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,776 publications
(1,591 citation statements)
references
References 138 publications
30
1,504
1
19
Order By: Relevance
“…Two-photon absorption (TPA) is a well-studied process, widely used in nonlinear spectroscopy [19]. Single-beam TPA is a suitable process to exhibit how a scalar diamagnetic contribution can become both readily identifiable and dominant compared to other multipole contributions.…”
Section: A Application To Two-photon Absorptionmentioning
confidence: 99%
“…Two-photon absorption (TPA) is a well-studied process, widely used in nonlinear spectroscopy [19]. Single-beam TPA is a suitable process to exhibit how a scalar diamagnetic contribution can become both readily identifiable and dominant compared to other multipole contributions.…”
Section: A Application To Two-photon Absorptionmentioning
confidence: 99%
“…The evolution of such structure/activity design considerations has also pointed to π -conjugated quadrupolar molecules with such electron-donor and -acceptor units arranged symmetrically with respect to the centre of the molecule as having large two-photon cross sections in the NIR region [31]. This has led to a sizable effort into the development of new TPE chromophores [26,31,32], although as He and co-workers [26] pointed out, there is some difficulty in comparing the quantitative two-photon absorption cross-section values reported, since these have been measured by different techniques and under different conditions.…”
Section: (B) Multi-photon Excitationmentioning
confidence: 99%
“…Among them, ruthenium-nitrosyl complexes have been recognized as the most promising candidates in relation to their generally low toxicity, good stability, and ability to release exclusively NO· under light irradiation, [6] taking advantage of the noninvasive and highly controllable characteristics of light. Additionally, although most NO· donors require to be irradiated in the 300-500 nm domain, the use of the two-photon absorption (TPA) technique, [7][8][9][10][11] in which the molecules simultaneously absorb two photons instead of one, allows the use of optical radiation at the double of wavelength, that is, the 600-1200 nm therapeutic window tiary amine in the carbazole unit leads to redshifted chargetransfer transitions towards the electron-withdrawing Ru-NO fragment and hence enhanced two-photon absorption (TPA) properties. In contrast, the quantum yield of the NO· photorelease process is lower for the carbazole-containing complex.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that increasing the "push-pull" character of the π-conjugated skeleton usually leads to an increase in σ TPA in dipolar molecules. [7][8][9][10][11] Therefore, the idea of replacing the fluorenyl unit by a more donating fragment arises naturally.…”
Section: Introductionmentioning
confidence: 99%